Estado e política de saúde : uma análise do projeto mais médicos para o Brasil - Silva, Laerge Thadeu Cerqueira da (2023)
In order to meet health demands and in response to the protests of June 2013 in Brazil, which pointed to the lack of medical practitioners as one of the central problems of the National Health System (SUS), the federal government, through Provisional Measure No. 621 of July 2013, replaced by Law No. 12.871 of October 22nd, 2013, institutes the Mais Médicos para o Brasil Project (PMMB) (More Doctors for Brazil, in Portuguese), which focuses on improving the infrastructure of basic health centers, expanding and qualifying human resources for the SUS and urgently providing physicians for vulnerable and extreme poverty areas. Regarding the Emergency Provision element, implemented through the PMMB and regulated by Interministerial Ordinance No. 1.369 of July 2013, which aims to ensure the emergency provision of medical practitioners for health centers in socially vulnerable areas, the Mais Médicos Project was at the center of discussions on health policy, given its political and ideological aspects, as well as its capacity to respond to the problem within the SUS scope. Given the issues presented, this thesis aimed to analyze the PMMB as a state action, in its socio-historical, political and management aspects, in the period from 2013 to 2022, and its implication for the referred system. To this end, we sought to understand and analyze the sociopolitical context of creation and implementation of the PMMB, its structure and management model at the national level, as well as its effects on health policy. With respect to methodology, we used a qualitative approach, based on the historical-critical method of reality analysis, in three stages: literature review, document analysis, and semi-structured interviews conducted with national managers from the Ministry of Health and the Ministry of Education who were in strategic positions in the PMMB implementation process. Based on Gramscian thought, the research sought to discuss the relationship between state and health policy with the categories of Extended State and Civil Society, in order to point out its contradictions in the neoliberal context and in the Brazilian sociopolitical setting. As for the results found, it is important to highlight that the debate around the provision of physicians, as well as other categories in the scope of SUS, considering the regional particularities and the dimension of Brazil, must be treated not only as something urgent, but also as a solid public policy, presenting new institutional arrangements that can account for structural changes in SUS, establishing a comprehensive and universal care for the population. It is necessary to take advantage of PMMB’s legacy and to establish goals for the creation of the National Career for SUS, responding to Primary Health Care demands regarding the lack of health professionals. Therefore, for the necessary structural changes to take place in SUS, guaranteeing the expansion of access to health and, thus, the universalization of health, it is necessary to conduct counter-hegemonic disputes, confronting conservative forces and commodification, because only then will it be possible to guarantee and expand this right.